The Level of Readiness of the Directorates of Education In the Governorates of Gaza to Respond to The Corona Crisis and its Obstacles - Abu Hashish, Bassam (The Arab Journal of Administration, 2022)
The study aimed to identify the level of readiness of the directorates of education in the governorates of Gaza to respond to the crisis of Corona and its obstacles from the point of view of workers. The researcher in this study followed the mixed descriptive analytical method, which combines quantitative and qualitative analysis, and the sample of the study consisted of (216) workers in the directorates of education in the governorates of Gaza, representing approximately (20%) from the study population, as well as a sample of (9) general managers who had an open discussion using the focused group tool, which was the study tool besides the questionnaire relied on in data collection, one of the most important results of the study was: the overall degree of organizational readiness of the directorates of education in the governorates of Gaza to respond to the corona crisis as realized by the workers; In any case, there are no statistically significant differences at the level of significance (α ≤0.05) between the average sized estimates of the study sample for the level of readiness of the directorates of education in the governorates of Gaza to respond to the corona crisis attributable to the change of type and function, while there were differences attributable to the change in years of service, and for the benefit of workers whose years of service more than 10 years. There were also differences in the readiness of the workers to respond to the Corona crisis and in the identification of the readiness of the directorates of education to respond to the Corona crisis as a whole between the workers of the Directorate of East Gaza and those in the Directorate of West Gaza, and the differences were in favor of the workers in the Directorate of Western Gaza. Many of the difficulties in improving the readiness of the directorates of education in the Governorates of Gaza to respond to the Corona crisis have also been identified from the point of view of the workers, and have been mentioned in the study. In the light of the results, it recommended that the Ministry of Communications and Information Technology should provide mechanisms for the exchange of information at the local, regional and international levels, and put it in the service of the Ministry of Education with its directors. Also, the Ministry of Education, in cooperation with specialized centers, should hold regular training programmers on the use of all potential communication networks by the personnel of its directorates. The Ministry of Education has allocated part of its budget to manage the Corona crisis, and the ministry has been instructed to do so for directorates.